FOTOGRAFI POTRET INDONESIA DALAM KARYA-KARYA FOTOGRAFER KASSIAN CEPHAS DAN ANDREAS DARWIS TRIADI - Prasetyo, Andry (Institut Seni Indoensia Surakarta, 2010)
Kassian Cephas and Andreas Darwis Triadi are two most popular photographers who become benchmarks in the development of pa trait photography in Indonesialheir photos are able to bring them to higher position and are able to make Indonesia being in the same place to other developed notions in photography of their era. Analysis result through aesthetic approach of potrait photography towards potrait photos produced by Kassihan Cephas ( I 845 — I 912) and Andreas Darwis Triadi shows that the works are produced by the process of creating which is built of aesthetic values so that they are able to lift civilization of each photograph artist. The works are also produced by a good skill of photography technique as well as creativity skill with high aesthetic touch. It can be seen from the costume, make up, style, and property used increating woman portrait photography. But it also cannot leave the human practical needs to support their daily lives such as spiritual need and personal interest.Key words: Potrait Photography, Aesthetics, Kassian Cephas and Darwis Triadi.